CHAVIN OF HUANTAR AND ARCHAEOLOGICAL DEFINITION OF AN ANDEAN THEOCRATIC STATE - Tantaleán, Henry (2011)
In this article we propose that the archaeological site of Chavin de Huántar was the materialization and center of a Andean theocratic state. To give support to such proposal we argue a serie of archaeological indicators which ones raise from the accumulated and updated information as well as own observations. With such proposal inspired in the historical materialism we expect generate a discussion focused on the archaeological objects and that attend to the particular material conditions and to the historical trajectory of the central andes.